Influence of Microwave Radiation on Growth of Calcium Sulphate Crystal by Monte Carlo Method - YANG*, XIAO-QING; YANG, LI-JUN; HUANG, KA-MA (Asian Journal of Chemistry, 2009)
Microwaves are widely used in synthesis of biomaterials. Manyexperiments show that the crystal shape of biomaterials with microwavesynthesis is quite different from the one with conventional methodunder the same crystal conditions. In this paper, we analyze the influenceof microwave radiation on calcium sulphate crystal growth by MonteCarlo method and explain the reason for difference of shape. The resultsshow microwave can deduce the surface tension and viscosity so as toinfluence the crystal growth and shape.